Poválečné Německo tehdy – v nulté hodině (Czech Journal of International Relations, 2000)
Rebecca L. Boehling: A Question of Priorities - Democratic Reform and Economic Recovery in Postwar Germany. Berghahn Books, New York- Oxford 1998, 301 stran, ISBN 1-57181-159-1.